PENGARUH ASIMETRI INFORMASI, PENGUNGKAPAN MODAL INTELEKTUAL, DAN KUALITAS AUDIT TERHADAP BIAYA MODAL EKUITAS (Studi pada Perusahaan LQ 45 yang Terdaftar di Bursa Efek Indonesia Tahun 2012-2014) - Ningsih, Rini Dwiyuna (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The research examines the effect of asymmetry information, intellectual capital disclosure, and audit quality on cost of equity capital. This research was an empirical study using multiple regression analysis. The sample of this study was taken from LQ 45 companies listed on Indonesian Stock ExchangeÂ  at 2012-2014. The sample was taken using purposive sampling. The sample used was 23 companies with a total of 68 observations. Statistical methods using Multiple Linear Regression Analysis to test the hypothesis.The result of the research shows that asymmetry information, intellectual capital disclosure, and audit quality simultaneously are not affect on cost of equity capital. Partially, asymmetry information and intellectual capital disclosure are not affect on cost of equity capital, whereas audit quality are affect on cost of equity capital.Â Keywordsâcost of equity capital, asymmetry information, intellectual capital disclosure, and audit quality.